Naturally acquired antibodies to polymorphic and conserved epitopes of Plasmodium falciparum merozoite surface protein 3. - Osier, F; Polley, S; Mwangi, T; Lowe, B; Conway, D; Marsh, K (2007)
Many studies on the role of merozoite surface protein 3 (MSP3) in immunity against malaria have focused on a conserved section of MSP3. New evidence suggests that polymorphic sequences within MSP3 are under immune selection. We report a detailed analysis of naturally-acquired antibodies to allele-specific and conserved parts of MSP3 in a Kenyan cohort. Indirect and competition ELISA to heterologous recombinant MSP3 proteins were used for antibody assays, and parasites were genotyped for msp3 alleles. Antibody reactivity to allele-specific and conserved epitopes of MSP3 was heterogeneous between individuals. Overall, the prevalence of allele-specific antibody reactivity was significantly higher (3D7-specific 54%, K1-specific 41%) than that to a recombinant protein representing a conserved portion of C-terminal MSP3 (24%, P < 0.01). The most abundant IgG subclass was IgG3, followed by IgG1. Allele-specific reactivity to the K1-type of MSP3 was associated with a lower risk of clinical malaria episodes during a 6-month follow-up in individuals who were parasitized at the start of the malaria transmission season (Relative risk 0.41 with 95% confidence interval 0.20-0.81, P = 0.011). The potential importance of allele-specific immunity to MSP3 should be considered in addition to immunity to conserved epitopes, in the development of an MSP3 malaria vaccine.